Knowledge Management, Industry 4.0 and Islamic Perspective: a Literature Review - Ab. Razak, Siti Nazihah; Abd. Hamid, Nurulhusna; Pebrianti, Hera (Program Pascasarjana, UIN Alauddin Makassar, 2023)
This paper discusses the relationship between Industry 4.0 and Islamic Perspectives. The fourth Industrial revolution is substantially the following stage in the digitization of the manufacturing sector. It provides a new approach of doing business and new sources of creating value. Industry 4.0 involves big data analytics. This will expose to information including sensitive or undisclosed information. As a syumul deen, Islam outlines the rules in shariah law and the purpose is described in Maqasid Shariah. The main purpose is to create the goodness and to prevent the harm. It includes five principles which are protecting deen, protecting life, protecting mind, protecting generation and protecting wealth. As an inventor or user of technology, these five aspects should be considered before making any resolution, so that the digital products and data-based services comply with the Islam guidelines.